The Boundaries of Corporate Law and Trust Law: An Analysis of Locking v. McCowan - Anand, Anita; Iacobucci, Edward (McGill Law Journal / Revue de droit de McGill, 2016)
There is an increasing trend among real estate investment trusts (REITs) to employ corporate law duties in formulating the duties of trustees. We contend that this approach represents a fundamental misunderstanding of the trust versus corporate law. To illustrate this point, we examine the case of Locking v. McCowan, a decision that we claim underscores the conceptual uncertainty regarding the extent to which corporate law applies in the income trust context. We argue that the case takes into account the difference between trusts and corporations in certain aspects of the decision, while, in others, it blurs the distinction between the two.In support of our argument, we note that income trusts lack a separate legal personality and are thus fundamentally different from corporations. The law governing each form therefore is not, and ought not be, identical. To apply corporate law to the interpretation of trustees’ duties fails to acknowledge the absence of a distinct legal entity in the trust context, and the historically fundamental fiduciary relationship between trustees and beneficiaries (i.e., unitholders, in this context). We favour greater clarity in the drafting of the declarations of trust (DOTs) to reflect an understanding that corporate law fiduciary duties should not ground trustees’ duties. Simply importing corporate law fiduciary duties into the DOT undermines the certainty on which DOTs, and thus the income trust market, should operate.